The Implementation of Kuliah Kerja Nyata Information System for Higher Education - Indri Sulistianingsih; Ahmad Akbar; Suheri -; Muhammad Arya Winatra (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
This paper explores the implementation of a Kuliah Kerja Nyata (KKN) Information System for Higher Education. The KKN program is a mandatory community engagement program for Indonesian university students, which requires careful management and coordination between universities, students, and community partners. The paper discusses the benefits of implementing a KKN Information System, which can streamline the process of managing student placements, community partnerships, and program logistics. The paper also presents various research methods, such as system design, database design, information system design, testing, evaluation, and improvement, which can be used to effectively develop, test, and refine the KKN Information System to meet the specific needs of the university and its stakeholders. Ultimately, the implementation of a KKN Information System can help universities better manage their KKN programs, while providing students with a more meaningful and impactful community engagement experience.